Oral health-related quality of life in orthodontics: a cross sectional study on adolescents and adults in orthodontic treatment in Kuantan, Pahang - Zubir, Muhammad Ikram; Iskandar, Muhammad Hanis; Mohd Ibrahim, Mohamad Shafiq; Cheong, Joo Ming (2022)
Introduction: Orthodontic treatment is always complementary to oral health-related quality of life (OHRQoL). The main reasons patients seek orthodontic treatment are due to aesthetics, oro-facial functionality, and psychological wellbeing. As known, orthodontic treatment is relevant in patients with malocclusion problems or facial disharmony. The Oral Health Impact Profile (OHIP) is an instrument frequently used to evaluate the patient’s subjective perception of oral well-being. This study aimed to assess the OHIP subscale’s impact on OHRQoL and to compare the OHRQoL between adolescents and adults. Materials and Methods: A total of 160 subjects (60 adolescents and 100 adults) undergoing orthodontic treatment completed the Malaysian Oral Health Impact Profile (S-OHIP(M)) to assess OHRQoL. The instrument consisted of 14 items grouped into 7 subscales which were (i) functional limitation, (ii) physical pain, (iii) psychological discomfort, (iv) physical disability, (v) psychological disability, (vi) social disability, and (vii) handicap. Mann-Whitney U and Kruskal Wallis test was applied to compare the OHRQoL between both age groups and demographic characteristics. Results: There is a statistically significant difference in median score for quality of life between adolescents 12(9) and adults 16(8). Physical pain had the highest impact on OHRQoL in both groups whereas social disability had the least impact for both groups. Conclusions: Our study showed that the adult groups reported a higher score of impact on OHRQoL compared to adolescent groups. In addition, adolescents and adults reported physical pain had the highest impact on OHRQoL during orthodontic treatment and social disability was the least affected factor in OHRQoL.